2015
DOI: 10.1002/ijc.29615
|View full text |Cite
|
Sign up to set email alerts
|

A novel genomic signature reclassifies an oral cancer subtype

Abstract: Verrucous carcinoma of the oral cavity (OVC) is considered a subtype of classical oral squamous cell carcinoma (OSCC). Diagnosis is problematic, and additional biomarkers are needed to better stratify patients. To investigate their molecular signature, we performed low-coverage copy number (CN) sequencing on 57 OVC and exome and RNA sequencing on a subset of these and compared the data to the same OSCC parameters. CN results showed that OVC lacked any of the classical OSCC patterns such as gain of 3q and loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The disconnect between dysplastic features and behaviour is shared with verrucous carcinoma which has a distinct molecular signature (Samman et al, 2015) probably shared with verrucous dysplasia, and possibly distinct from other dysplastic lesions (Okoturo et al, 2018).…”
Section: Dys Pl a S Ia In Verrucous And Papill Ary Le S I On Smentioning
confidence: 99%
See 1 more Smart Citation
“…The disconnect between dysplastic features and behaviour is shared with verrucous carcinoma which has a distinct molecular signature (Samman et al, 2015) probably shared with verrucous dysplasia, and possibly distinct from other dysplastic lesions (Okoturo et al, 2018).…”
Section: Dys Pl a S Ia In Verrucous And Papill Ary Le S I On Smentioning
confidence: 99%
“…No standardised criteria exist for the histopathological diagnosis of PVL and the clinical features remain paramount for establishing the diagnosis, particularly a predilection for palatal and gingival mucosa, older female patients and lack of association with risk factors. Whether there is a clear molecular distinction between PVL and other OPMDs with dysplasia remains unclear, though numerous differences are identified (Okoturo et al, 2018) and a distinct molecular signature is proposed for verrucous carcinoma (Samman et al, 2015).…”
Section: Dys Pl a S Ia In Prolifer Ative Verrucous Leukopl Akiamentioning
confidence: 99%
“…Genetic alterations are involved in polymorphism, point mutation, deletion, and other alterations. Previous investigation mainly focused on gene profiling (47,48).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Moreover, copy number and exome sequencing showed that OVC lacked classical OSCC patterns (e.g., gain of 3q and loss of 3p) and exhibited fewer genomic rearrangements compared to OSCC. Additionally, OVC samples lacked mutations in genes commonly associated with OSCC (TP53, NOTCH1, NOTCH2, CDKN2A, and FAT1) . Here, we compared for the first time in the literature the expression of the components of the Akt/mTOR pathway between OSCC and OVC.…”
Section: Discussionmentioning
confidence: 99%